Cinema and spectatorship - Mayne, Judith (Sightlines (London, England), 1993)
Cinema and Spectatorship is the first book to focus entirely on the history and role of the spectator in contemporary film studies. While 1970s film theory insisted on a distinction betweeen the cinematic subject and film-goers, Judith Mayne suggests that a very real friction between "subjects" and "viewers" is in fact central to the study of spectatorship. In the book's first section Mayne examines three theoretical models of spectatorship: the perceptual, the institutional and the historical, while the second section focuses on case studies which crystallize many of the issues already discussed, concentrating on textual analysis, the d̀isrupting genre', s̀tar-gazing' and finally the audience itself. Case studies incude the place of the spectator in the textual analysis of individual films such as The Picture of Dorian Gray; the construction of Bette Davis' star persona; fantasies of race and film viewing in Field of Dreams and Ghost; and gay and lesbian audiences as "critical" audiences. The book provides a very thorough and accessible overview of this complex, fragmented and often controversial area of film theory